Metode Latent Dirichlet Allocation dalam Pemodelan Topik Headline Berita Online tentang Hukum dan Kriminal - Medea, Mega Jayanti; Rantung, Vivi Peggie; Kembuan, Olivia (Program Studi Teknik Informatika, 2024)
Online news is a report about an event that is presented online by a news publishing company through an online news portal. Manado News is a news portal that presents news online which is divided into several categories. This study aims to analyze the data on news titles on the Manado News online news portal, Legal and Criminal category, to find out the crimes that are rampant and reported on this news portal. The analysis is carried out by implementing one of the methods in topic modeling, namely Latent Dirichlet Allocation. This method is used to find the topic of discussion in a document with a large capacity and displays the words that appear the most in a topic. The data needed for modeling was obtained by scraping on the online news portal Manado News, with a span of five years, from April 2017 to April 2022. After the data was processed using the Latent Dirichlet Allocation method, one topic of discussion was found, namely conventional crime groups. The topic contains a number of words which are types of crime in the conventional crime category, namely, persecution, theft, murder, stabbing, motor vehicle theft, sexual abuse and liquor.